Identification of potential inhibitors against Staphylococcus aureus shikimate dehydrogenase through virtual screening and susceptibility test - Mengfan Zhu; Jinfeng Qu; Qi Deng (Journal of Enzyme Inhibition and Medicinal Chemistry)
Staphylococcus aureus shikimate dehydrogenase (SaSDH) plays a crucial role in the growth of Staphylococcus aureus (S. aureus), but absent in mammals and therefore a potential target for antibacterial drugs to treat drug-resistant S. aureus infection. In this study, a 3D model of SaSDH was constructed by homology modelling and inhibitors of SaSDH were screened through virtual screening. (-)-Gallocatechin gallate and rhodiosin were identified as inhibitors with Kis of 2.47 μM and 73.38 μM, respectively. Molecular docking and isothermal titration calorimetry showed that both inhibitors interact with SaSDH with a KD of 44.65 μM for (-)-gallocatechin gallate and 16.45 μM for rhodiosin. Both inhibitors had antibacterial activity, showing MICs of 50 μg/mL for (-)-gallocatechin gallate and 250 μg/mL for rhodiosin against S. aureus. The current findings have the potential for identification of drugs to treat S. aureus infections by targeting SaSDH.